The application of Maqasid al-Shari’ah into cartilage tissue engineering - Ahmad Radzi, Muhammad Aa'zamuddin; Zainuddin, Zainul Ibrahim; Hashi, Abdurezak Abdulahi; Sha'ban, Munirah (Kulliyyah of Allied Health Sciences, IIUM, 2016)
Tissue engineering approaches, being part of regenerative medicine have been applied in treating the articular cartilage diseases worldwide. It offers benefit to the humankind by improving healthcare economics, better treatment and quality of life among the osteoarthritic patients. It is felt that this promising field requires Islamic essences to be addressed in its concepts and practices. The paper begins with the discussion on the potential of cartilage tissue engineering in overcoming the harms that may impact the healthcare stakeholders (patients, providers, medical professionals, researchers and government). This will be followed by deliberations based on the five higher objectives of Islamic Law (Maqasid al-Shariah), namely, safeguarding of faith, soul, wealth, mind, and offspring. The deliberations illustrate a general idea of cartilage tissue engineering concept and practices in relation to what Islam champions. Islamic Law is comprehensive and incorporates the moral propositions to the medical discipline. It is presented that every legal ruling in Islam has a function to achieve the benefit to human beings or to protect against harm. The application of Maqasid al-Shariah can serve as a practical framework in healthcare setting especially cartilage tissue engineering. It is hoped that this paper will open further discourses to facilitate for a decree by the relevant authority pertaining to the experimentation and practice of tissue engineering, particularly cartilage tissue engineering.